Determining the volumetric characteristics of a passive linear electro-magnetic damper for vehicle applications. Issue 1 (1st January 2017) - Fow, A.; Duke, M.
Abstract: Previous research has shown that passive electromagnetic damping could be feasible for automotive applications, but there would be a severe weight penalty, particularly in light weight vehicles. With modern advances in permanent magnets the feasibility of passive electromagnetic dampers is re-examined. A model of a permanent magnet and coil system is developed and validated in small scale. This magnet model is used to model a dynamic damper system which is again tested. This dynamic model is then scaled up to a two degree of freedom system to determine the damping for a quarter car model. Two damper designs are created each of which would produce a damping coefficient of 1, 600 Ns/m. The proposed dampers require more than three times the volume of the equivalent hydraulic dampers.